Promosi produk dalam pendidikan dasar: Analisis promosi produk pada SDN 1 Ngijo Karangploso Malang - Aprilia, Chofifah Dwi (Maliki Interdisciplinary Journal, 2024)
This article explores strategies, objectives, and supporting and inhibiting factors in the context of product promotion in basic education. The main thing discussed in this article is the method used by SDN 1 Ngijo Karangploso in carrying out promotions. In an effort to improve the quality of learning, this research highlights key strategies, including the use of educational technology, development of innovative teaching materials, and collaborative approaches between stakeholders. The main goal of product promotion is to create an inspiring learning environment, increase student interest, and facilitate effective teaching, bringing a positive impact on the future of society. Even though it has positive potential, supporting factors such as active stakeholder involvement are key to success. On the other hand, challenges such as limited funding, unequal access, and implementation barriers are inhibiting factors that need to be overcome. This research calls for continuing to develop innovative, relevant and inclusive strategies in the promotion of educational products, to ensure that basic education is not only a transfer of knowledge, but also a stage for developing the full potential of each student.